The politics of starch: guilds, monopolies, and petitioning in late Elizabethan and early Stuart London - Paterson, E (Routledge, 2022)
Using petitioning campaigns to express their discontent to both civic and central authorities, London’s livery companies emerged as powerful opponents of monopolies in the late Elizabethan and early Stuart periods. This article focuses on one campaign launched by the Grocers’ Company in response to the monopolisation of the production of starch from 1588, analysing a petition by the company and a counter-response offered by the newly incorporated Starchmakers’ Company in 1608. It highlights not only the politics surrounding starch, but also the careful utilisation of specific rhetorical devices by both groups in their attempts to persuade the state to favour their cause. It thus contributes to understandings of the sophistication of Jacobean manuscript petitioning culture. The article concludes by suggesting the potential power of such petitioning campaigns, utilised by subjects to respond to the growing presence of powerful projectors and ‘odious’ patents of monopoly in the realm.